Un extraño viene a comer a mi mesa: la asistencia financiera y los leveraged buy outs - Tuesta Pasamar, Adrian (2023)
The following work develops financial assistance and leveraged buyouts or leveraged purchases in light of article 106 of the Ley General de Sociedades (Peruvian Companies Act). It is discussed whether this is a prohibited mechanism or not and its implications today in Peru. The objective is to give an answer about the prohibition or not of its use. It starts by explaining this way of financing in the market and to show its advantages its observations and why it is not within the legal prohibitions. A description of the current doctrine and a development of a personal position on the subject will be made.There is also the participation of prominent lawyers in the field who explain the usefulness and real impact that these operations have on the country’s legal practice. The main conclusions reached is that it is not a mechanism prohibited by the LGS, however, there must be a more precise regulation to protect the interests of the creditors and minority shareholders of the target companies in this type of mechanisms. What is undeniable is that this is a mechanism that has been in force for 40 years in markets around the world and facilitates the mobility of capital. It came to stay and it must be given the correct regulation, without restricting operations, but protecting the rights that correspond.